Analisis Determinan Ekspor Komoditas Tekstil: Studi Kasus China, Jerman, India, dan Indonesia - Herawati, Pipit (PT Literasi Nusantara Publisher, 2023)
The textile commodity is one of the long-term priority sectors of the manufacturing industry, as the textile industry is a relatively reliable sector. However, the value of textile exports fluctuates every year. This study aims to analyze the factors or determinants of the export value of textile commodities in China, Germany, India, and Indonesia in 2010-2019. The data used in this study is panel data, using the Ordinary Least Square (OLS) regression analysis method. The independent variables in this study are exchange rates, gross domestic product (GDP), foreign direct investment (FDI), inflation, and competitiveness represented by Revealed Comparative Advantage (RCA). The results of the analysis show that exchange rates, GDP, FDI, and RCA have a positive effect on the value of textile exports. While inflation has no significant effect on the value of textile exports. Based on the Hausman test conducted, it is known that the regression model obtained does not contain heteroscedasticity problems.